Weighted average velocity forward modelling of Rayleigh surface waves - Leong, Eng Choon (2013)
Forward modelling is an integral part of inversion analyses of surface wave tests to obtain ground stiffness or shear wave velocity profile. Current rigorous forward modelling methods are complex and can be computationally expensive. In this paper, a new forward modelling method, known as weighted average velocity (WAVe) method, is proposed. Phase velocity at a given wavelength, Vφ(λ), is widely accepted to be influenced by properties of soil layers within that wavelength. In WAVe method, the influence of soil properties is accounted for as Vφ(λ) is calculated as a weighted sum of the shear-wave velocity (Vs) of all the soil layers within one wavelength depth. The procedure to obtain Vφ(λ) and hence the dispersion curve of a multilayered soil profile using the WAVe method is outlined. The WAVe method was evaluated using eight published soil profiles with dispersion curves obtained from other forward modelling methods and comparisons showed excellent agreement. Inversion analysis using WAVe method is also illustrated. Due to its efficiency and ease of implementation, the WAVe method can provide real-time evaluation of soil profiles during surface wave tests in the field, which is beneficial for geotechnical site investigation purposes.